Additional support for a revised Gibbs analysis - Menger, Fredric M (Langmuir : the ACS journal of surfaces and colloids, 2010)
Gibbs-determined areas of >60 A(2)/molecule for many common surfactants cause rather small surface tension reductions when measured on a Langmuir film balance. This is inconsistent with an air/water interface being saturated throughout the steep linear decline in plots of surface tension versus ln [surfactant]. In support for a gradually populating interface in the linear region, we have found that sodium docosanyl sulfate lowers the surface tension by only 7 mN/m when compressed to 50 A(2)/molecule. When docosanyltrimethylmmonium bromide is compressed to 65 A(2)/molecule, the surface tension is lowered about 15 mN/m as compared to a 30-40 mN/m drop occurring within the range of typical Gibbs analysis. Saturation of the interface is often obscured by competitive micelle formation that levels the surface tension versus ln [surfactant] plot before saturation has a chance to do so